Wireless transceiver architecture : bridging RF and digital communications - Baudin, Pierre (Electrical engineer); IEEE Xplore (Online Service); Wiley (Chichester, West Sussex, United Kingdom : Wiley, 2015)
"Presents transceiver system design and architecture in terms of budgeting a transceiver, transceivers architectures, and algorithms for transceivers"--
Machine generated contents note: Foreword ix Glossary xiv I Somewhere between Maxwell and Shannon 1 Chapter 1 -- The digital communications point of view 3 1.1 Bandpass signal representation 4 1.2 Bandpass noise representation 36 1.3 Digital modulations examples 48 1.4 First transceivers architecture 73 Chapter 2 -- The Electromagnetism point of view 79 2.1 Free space radiation 79 2.2 Conducted propagation 107 2.3 The propagation channel 126 Chapter 3 -- The wireless standards point of view 161 3.1 Medium access strategies 161 3.2 Metrics for transmitters 169 3.3 Metrics for receivers 187 II Implementation limitations 205 Chapter 4 -- Noise 207 4.1 Analogue electronic noises 208 4.2 Noisy devices characterization 211 4.3 LO phase noise 259 4.4 Linear EVM 294 4.5 Quantization noise 298 4.6 Analogue vs. digital worlds conversions 322 Chapter 5 -- Nonlinearity 345 5.1 Smooth AM-AM conversion 346 5.2 Hard AM-AM conversion 440 5.3 AM-PM conversion, memory effect 449 5.4 Baseband devices 464 Chapter 6 -- RF Impairments 467 6.1 Frequency conversion 468 6.2 Gain and phase imbalance 489 6.3 Mixers implementation 508 6.4 Frequency planning 540 6.5 DC offset, LO leakage 548 III Transceivers dimensioning 553 Chapter 7 -- Transceivers budgets 555 7.1 Considered transceiver architecture 556 7.2 Budgeting a transmitter 557 7.3 Budgeting a receiver 599 Chapter 8 -- Transceivers architectures 661 8.1 Transmitters 661 8.2 Receivers 717 Chapter 9 -- Algorithms for transceivers 735 9.1 Transmit side 735 9.2 Receive side 774 Appendix 1 -- Correlations 799 Appendix 2 -- Stationarity 809 Appendix 3 -- Moments of normal random vectors 815 Bibliography 821 Index 829 .
Includes bibliographical references (pages 719-722) and index.
Also available in print.
Mode of access: World Wide Web
Description based on PDF viewed 10/24/2017.
Keywords: Radio -- Transmitter-receivers.; Electronic books